2013
DOI: 10.1016/j.ijcard.2012.03.063
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure-induced skeletal myopathy in spontaneously hypertensive rats

Abstract: Reduced myogenin and follistatin expression seems to participate in muscle atrophy while increased MRF4 protein levels can modulate myosin heavy chain isoform shift in skeletal muscle of spontaneously hypertensive rats with heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 55 publications
(72 reference statements)
3
45
0
5
Order By: Relevance
“…Although there is substantial evidence that myogenic regulatory factors are changed in HF-induced skeletal myopathy [12,29,36], our hypothesis that MRFs modulate MyHC isoforms distribution in diaphragm was not confirmed. Myogenin is frequently found in association with oxidative enzyme expression and seems to play a role in skeletal metabolism characterization [27,28,59].…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Although there is substantial evidence that myogenic regulatory factors are changed in HF-induced skeletal myopathy [12,29,36], our hypothesis that MRFs modulate MyHC isoforms distribution in diaphragm was not confirmed. Myogenin is frequently found in association with oxidative enzyme expression and seems to play a role in skeletal metabolism characterization [27,28,59].…”
Section: Discussionmentioning
confidence: 71%
“…At the time of euthanasia, we determined the presence or absence of congestive HF by assessing lung congestion (lung weight/body weight ratio > 2 standard deviations above Sham group mean) and right ventricular hypertrophy (right ventricle weight-to-body weight ratio greater than 0.8 mg/g) [34,35,36]. After euthanasia, the infarcted rats were subdivided in two groups: 1) MI/HF- rats with no evidence of HF (n=10), and 2) MI/HF+ rats with right ventricular hypertrophy and lung congestion (n=10).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…32 We have observed in heart failure rats that muscle atrophy was combined with changes in myostatin/follistatin expression. 22,33 Muscle disuse by bed rest can also contribute to protein catabolism. 26 The most important consequence of increased protein degradation is a reduction in myocyte cross-sectional area and muscle mass, which contributes to a reduction in physical performance and daily living activities.…”
Section: Imbalance Between Anabolic and Catabolic Processesmentioning
confidence: 99%
“…40 Also in heart failure, muscle loss pattern depends on experimental model, and both a slow-to-fast and a fast-to-slow fiber-type shift has been described. 33,41 Recently, Callahan and Toth 26 suggested that increased proteolysis and reduced protein synthesis mainly occur during disease exacerbation and hospitalization due to increased inflammatory and neurohormonal activation. As anabolic pathways are probably insufficient to recover muscle size and function to prehospitalization levels, efforts to prevent disease exacerbation should be emphasized.…”
Section: Imbalance Between Anabolic and Catabolic Processesmentioning
confidence: 99%